Production of lettuce in NFT hydroponic system at different planting seasons and irrigation regimes - Soares, Cláudio Silva; de Lima, Alde Cleber Silva; da Silva, Jeneilson Alves; Vilar, Marina Suenia de Araújo; da Silva, André Luiz Pereira [UNESP]; de Lima Junior, Joaquim Alves; Neto, José Félix de Brito (Southern Cross Publishing, 2020)
Hydroponics has drawn huge interests by Brazilians in semi-arid regions due to the lack of water and fertilizer use. The objective of this study was to evaluate the growth and yield of lettuce cultivars in the hydroponic system in two planting seasons and different irrigation regimes. The research was carried out in Campus II / UEPB and followed a 2 × 6 × 3 factorial scheme in randomized blocks, represented by two planting seasons (the summer and the winter), six lettuce cultivars (Elba, Great Lakes, Mimosa Rose, Simpson, American, Cristina), three irrigation regimes (15 min, 30 min, 45 min) and five replications. The hydroponic system used was the NFT. For nutrition, Hidrogood Fert® solution (Compound + Calcium + Iron) was applied. At the 40th day after sowing, green and dry leaf biomass, green stem biomass, leaf area, leaf area index and productivity were analyzed. After that, the variance analysis was performed by the F-test for 5% of probability and the Scott-Knott test for comparison of the averages. The high temperatures caused very small growth in the stem of the Simpson cultivars, independent of the irrigation regime used. Besides the highlight of the American cultivars, the other cultivars presented satisfactory performance in the climatic conditions of Lagoa Seca / PB.
Keywords: Lactuca sativa; NFT; Semiarid